American Neo-Colonialism: its emergence in the Philippines and Asia - Pomeroy, William J. (New York, 1970)
This original and provocative study focuses upon the conflicts over U. S. foreign policy, from the turn of the century to 1923, with reference to the course of expansion across the Pacific. The debate came to a head over the seizure of the Philippines and its bearing upon the Asian, particularly the China, policy of the United States. The author probes deeply into events and factors which determined the outcome of the debate..
Keywords: International relations 1900